Dampak Model Project Based Learning terhadap Kemampuan Berpikir Kritis Siswa Sekolah Dasar di Pasirjambu - Anwar Jamil Rohmutiyah; Rayi Siti Fitriani; Ety Sukaetini (STKIP Subang, 2026)
Critical thinking is an essential 21st-century skill that needs to be developed from elementary school, in line with the critical reasoning dimension of the Pancasila Student Profile in the Merdeka Curriculum. Observations at SDN Astakrama revealed that Natural and Social Sciences (IPAS) learning on the Life Cycle of Living Things topic in third grade was still dominated by teacher-centered lecture methods, resulting in passive students and low critical thinking skills. This study aims to determine students' critical thinking skills before and after the implementation of the Project Based Learning (PjBL) model, to analyze the improvement, and to measure the magnitude of the model's effect. The research employed a quantitative approach with a Quasi-Experimental method using a Nonequivalent Control Group Design. The population consisted of all third-grade students at SDN Astakrama in the 2025/2026 academic year, with a saturated sampling technique resulting in class III-A as the experimental group (27 students) and class III-B as the control group (28 students). Data were collected through tests, observation, and documentation, then analyzed using the Mann-Whitney U test, N-Gain test, and effect size test. The results showed that before treatment, the critical thinking skills of both groups were relatively equivalent (0.059 > 0.05). After treatment, the experimental group obtained a posttest mean of 56.78, higher than the control group's 40.29. The improvement fell into the moderate category (N-Gain 0.4209), with an effect size of r = 0.33, also moderate. It is concluded that Project Based Learning has a positive and significant impact on improving the critical thinking skills of third-grade elementary school students in IPAS learning.